2021
DOI: 10.24949/njes.v14i1.633
|View full text |Cite
|
Sign up to set email alerts
|

Water quality assessment of Raw and Chlorinated drinking water of a Residential University

Abstract: The safety of water is essential for life on earth. Drinking contaminated water can give rise to many health issues. Tohighlight the major causes of contamination in water, this study was carried out to determine the physicochemical andbacteriological quality of raw and chlorinated water. Raw and chlorinated water samples were obtained from three locations (zones) of a residential university (National University of Sciences and Technology, NUST). Ten physicochemicalparameters were analyzed (pH, Electrical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Z-III has no overhead storage tank and water following chlorination is directed towards DWDS. Previous studies by Kamal and Hashmi (2021) and Javed et al, 2022 revealed water contamination in all underground storage tanks. Consequently, we randomly selected one underground storage tank, as well as the overhead storage tanks of Z-I and Z-II, for monitoring bio lm formation.…”
Section: Study Area Descriptionmentioning
confidence: 80%
“…Z-III has no overhead storage tank and water following chlorination is directed towards DWDS. Previous studies by Kamal and Hashmi (2021) and Javed et al, 2022 revealed water contamination in all underground storage tanks. Consequently, we randomly selected one underground storage tank, as well as the overhead storage tanks of Z-I and Z-II, for monitoring bio lm formation.…”
Section: Study Area Descriptionmentioning
confidence: 80%